DESIGN & VALIDATION METHODOLOGY FROM A LIFE PREDICTION PERSPECTIVE FOR THE STRUCTURAL COMPONENTS OF A RECREATIONAL PRODUCT - Cristian, Iorga; Alain, Desrochers (European Scientific Journal, ESJ, 2014)
The paper outlines a design process flow diagram (methodology) that highlights the challenges of engineering design and allows both engineers and students to focus on the development of a creative, effective and profitable solution to meet particular life objective and additional criteria. A case study related to a recreational vehicle is also presented to validate the methodology. Therefore, to reach the objective of weight reduction for the structural subsystem in a hybrid roadster project, a methodology that allows the optimization of the design parameters according to several types of design criteria has been developed.